Masses, lifetimes and production rates of Xi(-) and Xi(+) at LEP 1 - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alderweireld, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; et al. (2006)
Measurements of the Ξ- and over(Ξ, ̄)+ masses, mass differences, lifetimes and lifetime differences are presented. The over(Ξ, ̄)+ sample used is much larger than those used previously for such measurements. In addition, the Ξ production rates in Z → b over(b, ̄) and Z → q over(q, ̄) events are compared and the position ξ* of the maximum of the ξ distribution in Z → q over(q, ̄) events is measured. © 2006 Elsevier B.V. All rights reserved.